In situ study of residual stress evolution in Zr(C,N)/α-Al2O3 and Zr(C,N)/κ-Al2O3 CVD multilayers during thermal cycling - Moreno, Maiara Fernanda (2019)
The present work analyses the residual stresses of thin films in coated cutting tools used in milling applications. Typical wear limitation is the formation of comb cracks, which lead to chipping and failure of the tools. The resistance to comb cracks depends on the ability of the coated tools to reduce the formation of thermo-mechanical cracks, which are originated in the coating and propagate into the carbide. By adjusting the residual stress condition of the coating/carbide substrate (which depends among others on the coefficient of thermal expansion of the layers, the processing method as well as the pre-or post-treatment) the resistance to comb crack failure can be improved. The Ti(C,N)/α-Al2O3 system is the most common used in the industry. Recently, an alternative coating with improved comb crack resistance based on Zr(C,N)/α-Al2O3 has been developed. In some applications the use of κ-Al2O3 is of advantage. In this work the residual stress analyses of Zr(C,N)/κ-Al2O3 and Zr(C,N)/α-Al2O3 coatings produced by (CVD) were carried out using Energy Dispersive X-ray diffraction. Furthermore, the residual stresses were analyzed \"in situ\" at cycling temperature conditions ranging from RT to 800 ºC in order to verify the influence of the different systems on the residual stress evolution and behaviour of the composites. In addition, the influence of micro-top-blasting on the residual stress of the thin films was investigated. It was observed that both the Zr(C,N)/κ-Al2O3 and Zr(C,N)/α-Al2O3 systems present similar residual stress cycling behaviour. The effect of the top-blasting process is confined to the α-Al2O3 layer, which develops high compressive residual stresses. The results of this work provides valuable information for the design of novel coating systems with enhanced resistance to comb cracks.